Stepwise Total Hip Arthroplasty with Lateral and Posterolateral Approaches: Intraoperative Imaging, Fixation Strategy, and Early Functional Outcomes - Roland Fazakas; Laura Ioana Bondar; Csongor Toth; Brigitte Osser; Iosif Ilia; Gabriel Roberto Marconi; Victor Niculescu; Ramona Nicoleta Suciu; Liviu Gavrila-Ardelean; Alexandru Pop (Life)
Background/Objectives: Total hip arthroplasty (THA) remains a widely utilized and effective intervention for patients with end-stage hip osteoarthritis. Although multiple surgical approaches and fixation techniques are available, their application in non-tertiary clinical settings is less frequently documented. This study primarily aims to provide an educational overview of stepwise THA procedures using intraoperative visual documentation, with a secondary, exploratory assessment of postoperative outcomes related to surgical approach and fixation strategy. Methods: A prospective observational study was conducted at Arad Clinical Emergency County Hospital between March 2023 and March 2024, involving 23 patients undergoing primary THA. Patients received either cemented or uncemented femoral components based on intraoperative bone quality. Procedures were documented using stepwise intraoperative photographs and postoperative radiographs. Recovery was assessed using the Harris Hip Score (HHS) and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) at both six weeks and six months postoperatively. Results: Both lateral (Hardinge) and posterolateral approaches provided adequate exposure with reproducible results. Cemented implants allowed for immediate full weight-bearing and were preferred in elderly patients with poor bone quality, while uncemented components were used in younger patients with good bone density, requiring a delayed weight-bearing protocol. Functional scores improved in both groups between six weeks and six months. At six weeks, the mean HHS was 87.6 ± 6.2 and WOMAC 18.3 ± 4.8; by six months, these improved to 91.8 ± 5.1 and 12.7 ± 3.9, respectively. Cemented fixation demonstrated slightly better outcomes at both time points; however, intergroup differences remained below the Minimal Clinically Important Difference (MCID) thresholds. Conclusions: Tailored surgical approaches and fixation strategies, guided by intraoperative assessment, result in favorable short- and mid-term recovery profiles in THA. The integration of intraoperative visual documentation and patient-reported outcome measures (PROMs) enhances procedural transparency while supporting evidence-based decision-making and surgical training.